2016
DOI: 10.4238/gmr.15017232
|View full text |Cite
|
Sign up to set email alerts
|

Genomic breeding value prediction for simple maize hybrid yield using total effects of associated markers, under different imbalance levels and environments

Abstract: ABSTRACT. The main objective of a maize breeding program is to generate hybrid combinations that are more productive than those pre-existing in the market. However, the number of parents, and consequently the number of crosses, increases so rapidly that the phenotypic evaluation of all the possible combinations becomes economically and technically infeasible. In this context, predicting the performance of the most promising genotypes may increase the genetic gains with increased selection intensity and reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…We found that the genetic diversity revealed by SNPs (H E : 0.083-0.142) is lower than that evaluated from SSRs (H E : 0.294-0.487) (Yin et al, 2019). While SNP markers are bi-allelic, SSR markers are multi-allelic (Cantelmo et al, 2016), which likely increases rates of heterozygosity and allelic richness at these loci. For example, Fischer et al (2017) compared the effects of microsatellite and SNPs in estimating genomic diversity of Arabidopsis halleri, and also found that H E indices estimated from SNPs were overall lower than those estimated from SSRs.…”
Section: Discussion Genetic Diversity and Geographical Differentiation Within A Albusmentioning
confidence: 62%
“…We found that the genetic diversity revealed by SNPs (H E : 0.083-0.142) is lower than that evaluated from SSRs (H E : 0.294-0.487) (Yin et al, 2019). While SNP markers are bi-allelic, SSR markers are multi-allelic (Cantelmo et al, 2016), which likely increases rates of heterozygosity and allelic richness at these loci. For example, Fischer et al (2017) compared the effects of microsatellite and SNPs in estimating genomic diversity of Arabidopsis halleri, and also found that H E indices estimated from SNPs were overall lower than those estimated from SSRs.…”
Section: Discussion Genetic Diversity and Geographical Differentiation Within A Albusmentioning
confidence: 62%